Manifestations of allostatic load in residents of radiation contaminated areas aged 18–24 years - V. L. Sokolenko; S. V. Sokolenko (Regulatory Mechanisms in Biosystems, 2019)
We studied the features of allostatic load (AL) in 100 students aged 18–24 years old who, from birth to adulthood, lived in the territories assigned to the IV radiation zone after the Chornobyl accident (density of soil contamination by isotopes 137Cs 3.7–18.5∙104 Bq/m2) and underwent prolonged exposure to small doses of ionizing radiation. The examined students did not have any clinical signs of the immune-neuroendocrine system dysfunction. 50 people had signs of vegetative-vascular dystonia syndrome (VVD), 48 had signs of moderate hyperthyroidism and 21 had signs of moderate hypothyroidism. During the examination session, as a factor of additional psycho-emotional load, in 66 of the examined the immunoregulatory index CD4+/CD8+ went below the lower limit of the homeostatic norm, in 62 of the examined low density lipoprotein cholesterol (LDL-C) exceeded the upper level. The relative risk (RR) and attributable risk (AR) of the participation of potential secondary factors of allostatic load formation in CD4+/CD8+ immunoregulatory index going below the lower limit were calculated. The presence of statistically significant relative risk of participation in the formation of suppression of the index CD4+/CD8+: the state of hyperthyroidism, state of hypothyroidism, vegetative-vascular dystonia syndrome, higher than normal LDL-C. When the examined students combined the signs of hyperthyroidism, vegetative-vascular dystonia syndrome and higher level of LDL-C; with combination of signs of hypothyroidism, vegetative-vascular dystonia syndrome and higher level of LDL-C. The attributable risk in all cases exceeded 0.10, which confirmed the importance of some of these factors and their complexes in the formation of the effect of reduced immunoregulatory index. The CD4+/CD8+ index can be considered an important biomarker of AL and premature age-related changes in the immune system in residents of radiation-contaminated areas. The risk of AL formation in the case of occurrence of a complex of mediated secondary biomarkers (vegetative-vascular dystonia syndrome, thyroid dysfunction, hypercholesterolemia) is higher compared to their individual significance.